Implementation of e-learning by vocational-school teachers of mechanical engineering - Widarto, Widarto; Wijanarka, Bernardus Sentot; Wibowo, Aris Eko (Jurnal Cakrawala Pendidikan, 2024)
Electronic-based learning or commonly called e-learning or online learning has become an important component of learning in vocational high schools considering the need to prepare students to face future challenges. The aim of this study is to evaluate teachers' readiness for online learning, identify difficulties faced by teachers, identify the e-learning platforms used, and examine the learning methods used. The research respondents were 118 vocational-school teachers in mechanical engineering throughout Indonesia. The research instrument was a questionnaire distributed online using Google Form, and the results were analyzed using descriptive statistics. The results of the study revealed that most Mechanical Engineering Vocational School teachers stated that they were not ready to implement e-learning, and the readiness of productive teachers was lower than that of adaptive teachers. The main difficulties experienced by teachers in e-learning are in the aspects of learning facilities and implementation of the learning process. The digital platform most used by teachers is social media, followed using video conferencing, and LMS is the platform that is used the least. Teachers have implemented student centered learning methods combined with teacher centered learning in online learning. Learning innovation is needed in the form of integration of methods, platforms and media that can accommodate teachers' difficulties, especially for productive subjects that require practice to form hard skills competencies